Azimuthal anchoring coefficients of nematic liquid crystals on polystyrene brushes formed at the air surface of block copolymer monolayers. Issue 7 (27th May 2020) - Iwata, Naoto; Yoshioka, Yuzuka; Yazawa, Kenta; Tokita, Masatoshi
ABSTRACT: A nematic liquid crystal (NLC) on a diblock copolymer monolayer shows Néel walls under a polarised optical microscope and the azimuthal anchoring coefficient ( A φ ) is estimated from the width of the wall. The block copolymer consists of polystyrene (PS) and poly(3-(triethoxysilyl)propyl methacrylate) (PTESPMA) segments. A monolayer of a pair of PS and PTESPMA layers was prepared by spin coating a copolymer solution on a glass substrate, followed by annealing using methylcyclohexane, exposure to hydrochloric acid vapour and rinsing with acetone. The PS layer is at the air surface and exhibits a thickness five times larger than the radius of gyration of the PS chain, which suggests that the PS chains are more extended towards the air surface, adopting a brush conformation. The A φ is 6 × 10 −6 J m −2 at 25°C and slightly decreases to 3 × 10 −6 J m −2 with increasing temperature up to 90°C. On the other hand, the A φ on a high-density PS brush, which is prepared via surface-initiated polymerisation method, decreases from 8 × 10 −6 to 3 × 10 −7 J m −2 with increasing temperature in the same range. Graphical abstract: uf0001